Portrait of musician and instrument maker Colin Offord, 2003 - Cosgrave, Paul 1950- (Canberra : National Library of Australia, 2003)
"This image shows musician and instrument maker, Colin Offord, in a studio portrait with his two main instruments - The Great Island Mouth Bow (two instruments free standing, background) and Colin's Australasian Belly Bow. Offord makes and plays instruments ranging from his own belly bows and harmonic Moon Bells to conch shells and flutes made from a Kangaroo bone and an eagle feather. The Great Island Mouthbow can be plucked, bowed, percussed and sung through. Offord was originally a painter and graphic artist. In 2003 his ensemble was known as The Great Bowing Company. He has now formed a new band called Spiral Sound. He left Leura last year to live in Calgary, in Canada, in order to be closer to European venues, particularly in Belgium. He has played with Belgian symphony orchestras and bemoans the fact that whilst he is well known in Europe, there is little interest in his music and the visceral arts in general in Australia. However, he has now moved back to Sydney, while continuing to perform overseas. "He is like a modern troubadour with his artistic crossover of Celtic, Aboriginal, Medieval and Asian musics. His performances are enchanting, effortless and always an exciting event", wrote Antoine Legat in Belgium's Cultuur Magazine."--Acquisition documentation.
Title from acquisition documentation.
Acquired in digital format; access copies available online.
Mode of access: Internet via World Wide Web.
Keywords: Offord, Colin -- Portraits; Musical instrument makers -- Australia -- Portraits; Musicians -- Australia -- Portraits; Bowed stringed instruments -- Australia -- Portraits; Musical instrument makers; Musicians